EFEKTIVITAS MODEL PEMEBELAJARAN KOOPERATIF JIGSAW UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATERI AL-QUR’AN - Sagiman, Sagiman; Tri Setyo, Tri Setyo; Santoso, Moch; Hakim, Ibnu (Al Fattah Ejournal Sma Al Muhammad Cepu, 2023)
This research is Classroom Action Research which examines the implementation of cooperative learning “Jigzaw” to increase the students’ participation and achievement. Observation and test were used to know the students’ participation and achievement. The results had two cycles, and every cycle consists of six steps; orientation, division of origin group, determining materials, forming expert group, discussion, and presentation. The result showed there was development from cycle 1 to cycle 2, the percentage of students whose activity was in the low category continued decrease, namely 55%-13%-4% while moderate category is from 25%-35%-30%. while the high category is from 20%-52%-66%. The result showed students who passed KKM increased from 61 % to 86%, it means there were 97% of students who passed KKM. From the result above using jigzaw successfully increased students;